PHARMACOLOGICAL ASPECTS OF BOTULINUM TOXIN TYPE A AS A COADJUVANT IN ITS THERAPEUTIC : AESTHETIC APPLICATIONS. AN INTEGRATIVE LITERATURE REVIEW - Sonego Furlan, Andreza; Pilon Muknickas, Daniella; Bonetti, Elka; Ribeiro Marques, Brenda; Barbosa Salvati, Ronaldo; Aparecida de Andrade Pinto, Stella; Teruo Suguihara, Roberto (Health and Society, 2023)
Botulinum toxin type A comes from a protein complex of the bacterium Clostridium botulinum, used in pharmacology and in aesthetic treatments to reduce facial expression lines. The objective of the study was to understand the pharmacological benefits and risks of using botulinum toxin Type A for aesthetic purposes. For this, the historical aspects, taxonomy, and physiology of Clostridium botulinum were presented; and the use of botulinum toxin type A was discussed in aesthetic procedures, its advantages, and disadvantages. The study methodology was a literature review of qualitative descriptive research, of works published between 2002 and 2019, in the databases VHL, BIREME, SCIELO, CNPQ and college websites. Among the results, botulinum toxin type A in aesthetic facial treatments, botulinum toxin reduces the wrinkles of the upper third of the face, such as raising eyebrows, frontal and cervical lines, among others; complications are pain, erythema and ecchymosis, the problems occur mainly in treatments such as pharmacology, due to high dosages in the body, or when associated with any health problem or medication. It is concluded that the prevention of complications with botulinum toxin type A is the anamnesis procedure before starting the facial treatment, so that the professional can raise problems of contraindication of this substance.